Efficacy of Dynamic Еlectric Neurostimulation in the Complex Treatment of Patients with Arterial Hypertension - Victor A. Drobyshev; Lubov A. Shpagina; Andrey A. Vlasov; Marina V. Umnikova; Alexandra V. Mashanskaya (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2023)
Low adherence of patients with arterial hypertension to regular therapy increases the risk of fatal complications. Patients' motivationfor treatment can be increased by non-drug methods of exposure.Aim. To evaluate the effectiveness of the inclusion of dynamic electric neurostimulation in the treatment regimens of patients witharterial hypertension to control blood pressure (BP) levels.Material and methods. 60 patients aged 25-55 years old with verified diagnosis of arterial hypertension (I-II degree) were examinedin Novosibirsk City Clinical Hospital № 2. The 1st group (the main group, n=30) received a 15-day course of acupuncture of the neiguan point from the apparatus «Leomax-Cardio Compact» in addition to the standard therapy; the 2nd group (comparison group,n=30) received the standard treatment complex and simulation of acupuncture exposure. Patients were trained to use the «Leomax-Cardio compact» device and to perform self-monitoring of arterial pressure (BP) from the UA-767 (AND) device. The checkup includedcarbohydrate, lipid metabolism, kidney function, electrocardiography assessment, daily BP monitoring.Results and discussion. By the end of observation, the target BP levels in the 1st group patients were 70.0% achieved, we managedto correct the variability of systolic and diastolic BP relative to the initial values by 1.3 and 1.6 times respectively, to decrease the rate ofmorning rise of systolic BP by 1.3 times, to increase the frequency of the variant of daily BP profile "dippers" by 1.3 times and to decreasethe number of "non-dippers" by 1.7 times, which differed from the similar indicators in the 2nd group. Electro-puncture with «Leomax-Cardio Compact» may have an antihypertensive effect due its effect on the suprasegmental parts of the autonomic nervous system.Conclusion. Inclusion of electropuncture from the device Leomax-Cardio Compact in the treatment regimens of patients withuncomplicated arterial hypertension allows to correct the neurovegetative regulation, which allows effective control of the targetvalues of systemic hemodynamics.